BURNOUT PADA MAHASISWA KEDOKTERAN: TINJAUAN PUSTAKA - Az Zahra, Aliya Rifani; Rika Lisiswanti; Tetra Arya Saputra; Dwita Oktaria (Nusantara Hasana Journal, 2025)
Burnout in medical students is a growing concern due to the high academic demands and psychosocial stressors during their education. This article aims to review the prevalence of burnout in medical students, risk factors, and prevention strategies reported in various studies. The method used was a literature review, which included searching national and international scientific articles through databases such as Google Scholar and PubMed, using keywords related to burnout and medical students. The inclusion criteria were articles published within the last ten years and relevant to the topic. The method used was a literature review of relevant national and international articles from the last ten years. The results showed that the prevalence of burnout in medical students varies across institutions and countries, with the majority of students experiencing low to moderate levels of burnout, but a significant proportion experiencing moderate to high levels of burnout. Key risk factors include low self-efficacy, low emotional intelligence, heavy academic load, educational stage, gender, and pressure to demonstrate professional competence. Conversely, intrinsic motivation, resilience, and social support act as protective factors. Various recommended prevention strategies include adaptive coping, time and stress management, maintaining physical health and sleep quality, and institutional support through mentoring programs and counseling services. In conclusion, burnout in medical students requires serious attention and comprehensive management to maintain psychological well-being and ensure the continuity of medical education.